Motivasi Kerja Bellboy pada Masa Pandemi: Pendekatan Metode Ranking - I Putu Arya Mahardika; I Gusti Ayu Putu Wita Indrayani; I Gede Darmawijaya (Program Studi Manajemen Divisi Kamar, 2022)
The purpose of this study is to investigate the job motivation of bellboys at the Hotel SBR located in Nusa Dua's exclusive area during the COVID-19 pandemic. Data for this study was gathered through interviews, documentation, and the distribution of questionnaires. In this study, the data was analyzed both descriptively and qualitatively using the ranking approach. According to the findings of the study, bellboys at the Hotel SBR were more motivated to work to earn money or salaries to support the demands and interests of their families during the COVID-19 epidemic. According to Maslow's Hierarchy of Needs Theory, physiological needs acquire the first ranking, which is supported by indicators such as salary, clothing, and nourishment, which are the primary needs that are acceptable during the COVID-19 pandemic. The four remaining needs are non-essential needs to be obtained during the COVID-19 pandemic, particularly the need for security in the second ranking, which is supported by indicators such as pension remuneration, health insurance, and employment status granted, followed by social needs in the third ranking. The social needs are supported by indicators such as working connections with coworkers, supervisors, and fellow firms. The indicators in the final ranking, self-actualization requirement, on the need for appreciation, justify the final ranking.